On deferred weak statistical convergence - Ercan, Sinan; Altin, Yavuz; Et, Mikail; Bhardwaj, Vinod K. (Springernature, 2020)
The aim of the present work is to introduce the concepts of deferred weak statistical convergence and deferred weak Cesaro summability on normed spaces. We prove some properties with related to these concepts and we also give some new related notions and some inclusion relations with examples.
Keywords: Deferred statistical convergence; Weak statistical convergence; 40A05; 40G15